Keeping cows cool - Smith, John F., 1962-; Harner, Joseph P.; Brouk, Michael J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Heat stress occurs when a dairy cow’s internal heat load is greater than her capacity to lose unwanted heat to the environment. Effects of heat stress include: increased respiration rate, increased water intake, increased sweating, decreased dry matter intake, slower rate of feed passage, decreased blood flow to internal organs, decreased milk production, and poor reproductive performance. Lower milk production and reproductive performance cause economic losses to dairy producers. The ordered priorities for reducing heat are: increasing water availability; providing shade in the housing areas (both dry and lactating cows) and holding pen; reducing walking distance to the parlor; reducing time in the holding pen; improving holding pen ventilation and freestall ventilation; adding cooling for the holding pen and exit lane; cooling close-up cows (3 wk before calving); cooling housing for fresh and earlylactation cows; and cooling housing for midand late-lactation cows.
Keywords: Dairy; Heat stress; Cooling techniques